Congenital absence of the vermiform appendix: a rare but important entity - Moissinac, Kevin; Chong, S. T. B. (Japan International Cultural Exchange Foundation, 1998)
Although Congenital abnormalities of the vermiform appendix are rare it would stand surgeons in good stead to be familiar with these potentially perplexing entities. Absence of the vermiform appendix was found in a patient who underwent appendicular exploration. The rarity of the condition, its clinically perplexing potential and possible medicolegal implications have prompted this case report.